Small and Medium Enterprise Development Experience and Policy in Japan and the Philippines: Lessons and Policy Implications - Cielito F. Habito; Ronald J. Tamangan; Frances Josef (Philippine Institute for Development Studies (PIDS), 2004)
The role of SMEs in economic development has been well recognized. SMEs have been regarded as an important contributor to employment generation and wealth creation in a developing economy. Ironically, however, SMEs have been discriminated against considering a raft of issues. In almost all countries, there is either a separate policy statement for SMEs (or for micro or cottage industries) or a general industrial policy statement with some portions of it relating to SMEs. Philippine SME development policies that have been set in place may have been in light of major Philippine industrial development policies. Historically, the common thread that binds Philippine industrial policies has been the emphasis on policies regarding expansion of exports, increases in foreign investments, development of the private sector, and enhancement of domestic linkages. Moreover, there might have been industrial policies that may have undermined SME development because of inherent scale biases. Inroads regarding SME development have been realized in the economy thus far, but Philippine SMEs can still derive some lessons from the Japanese experience, particularly Japans practices regarding subcontracting and clustering. There is also a need to realize that it is now insufficient to address commonplace themes and roadblocks experienced by Philippine SMEs identified through historical experiences. Nowadays, it is inescapable to acknowledge that concerns regarding SMEs will have to be considered and addressed in light of globalization, which is most easily comprehended in terms of international trade. Bilateral trade cooperation is mutually beneficial. One way for Japan to encourage Philippine SME development, as part of bilateral trade cooperation, is to identify and open some Japanese markets to Philippine SME exports. Hence, sector (or even subsector) identification in general, and product identification in particular, is a necessary first step to this end.
Keywords: 330; industrial policies; bilateral agreements; small and medium enterprises (SMEs); Internationale Wirtschaftsbeziehungen; Industriepolitik; KMU; Vergleich; Japan; Philippinen